Factors affecting customer’s demand towards life insurance: a case study on rural communities in Sg Lembing / Anis Syuhada Shahid - Shahid, Anis Syuhada (Faculty of Business and Management, 2015)
This research is to identify the factors that can affect the demand for life insurance in rural area Malaysia especially at Sg Lembing, Pahang. The study will be gather using 100 set of questionnaire as it will distributed at rural area Sg Lembing, Pahang. The data will be interpreted using multiple regression analysis to explain the relationship on how financial literacy, savings and price toward subscription of life insurance. The most factors influence the demand of life insurance purchasing decision is financial literacy and following by savings and price. Overall , there is significant relationship between dependant variable and independent variables. Based on this study, it is good to understanding on the demand for life insurance in the rural area in Malaysia.